The effectiveness of television commercial toward Malaysian Audiences' Behavior / Amirul Asyraf Azman - Azman, Amirul Asyraf (2018)
Television commercial is one of the medium in promoting product, brand, and also create awareness towards audiences. But, some of the audiences' behaviour was affected by television commercial. This research is about the effectiveness of television commercial toward Malaysian audiences' behaviour. The researcher uses three research objectives in order to proceed with the research which is to study the effectiveness of television commercial towards audience, understand the uses of celebrity endorsement to change audiences' behavior, and also investigate the airtime for audience watch the television commercial. This research uses quantitative research method to collect data which is by using survey. After all the data being collected it will be transfer to the Statistical Package for the Social Sciences (SPSS) and was take out the important data to be discuss in the data analysis and findings. This research gathers all the information needed and conclude the research in the final chapter of this research.